The Elimination of Broker Voting in Director Elections - Ali Akyol; Konrad Raff; Patrick Verwijmeren (Tinbergen Institute, 2012)
After pressure from shareholder activists, proxy advisory firms, and the New York Stock Exchange, the Securities and Exchange Commission has eliminated uninstructed broker voting in director elections. We observe that average director approval rates remain high after the change in regulation, while the probability of a director being voted off the board remains low. In addition, we find no evidence of significant wealth effects of the change in regulation. We do find that firms are increasingly letting shareholders ratify their auditors after the change in regulation, which helps in establishing a quorum.
urn:NBN:nl:ui:31-1871/38513
Keywords: G34; G38; 330; Broker voting; shareholder empowerment; Securities and Exchange Commission; board effectiveness; Board of Directors; Shareholder Value; Finanzmarktaufsicht; USA